The Soviet quest for economic efficiency : issues, controversies, and reforms - Feiwel, George R. (New York : Praeger, 1967)
This volume provides an analysis of the problems confronting Soviet leaders in their efforts to improve the structure and function of their system of industrial management. Chapter 1 traces the early efforts during the twenties to map out a strategy of industrialization and concludes with the economics of the Stalinist period. Chapter 2, provides a summary outline of the general characteristics of Soviet planning methodology and of the shifting patterns of industrial administration. A resume of the industrial supply system completes this chapter. Chapter 3 continues the same topic of planning methodology, as it relates to such questions as prices, investment, plan fulfilment and incentives. Chapters 4 and 5 are devoted to a survey of the forces and ideas that are pressing for changes in the management of Soviet industry. Chapter 6, deals with the official implementation of the industrial reform.
Bibliography: p. 415-420.
lje 23/10/18
Loans
Keywords: Economic development; Economic growth; Soviet Union